Protective immunity to Mycobacterium tuberculosis infection by chemokine and cytokine conditioned CFP-10 differentiated dendritic cells. - Nasir Salam (Public Library of Science (PLoS), 2008)
Background Dendritic cells (DCs) play major roles in mediating immune responses to mycobacteria. A crucial aspect of this is the priming of T cells via chemokines and cytokines. In this study we investigated the roles of chemokines RANTES and IP-10 in regulating protective responses from Mycobacterium tuberculosis (M. tb) 10 kDa Culture Filtrate Protein-10 (CFP-10) differentiated DCs (CFP10-DCs). Methods and findings Infection of CFP10-DCs with mycobacteria down-modulated RANTES and IP-10 levels. Pathway specific microarray analyses showed that in addition to RANTES and IP-10, mycobacteria infected CFP10-DCs showed reduced expression of many Th1 promoting chemokines and chemokine receptors. Importantly, T cells co-cultured with RANTES and IP-10 conditioned CFP10-DCs mediated killing of mycobacteria from infected macrophages. Similarly, T cells recruited by RANTES and IP-10 conditioned CFP10-DCs mediated significant killing of mycobacteria from infected macrophages. IFN-gamma treatment of CFP10-DCs restored RANTES and IP-10 levels and T cells activated by these DCs mediated significant killing of virulent M. tb inside macrophages. Adoptive transfer of either RANTES and IP-10 or IL-12 and IFN-gamma conditioned CFP10-DCs cleared an established M. tb infection in mice. The extent of clearance was similar to that obtained with drug treatment. Conclusions These results indicate that chemokine and cytokine secretion by DCs differentiated by M. tb antigens such as CFP-10 play major roles in regulating protective immune responses at sites of infection.